Avaliação dos aspectos orofaciais, com ênfase nas funções espiratórias e mastigatórias, em indivíduos com e sem Hipomineralização Molar-Incisivo (HMI): estudo observacional - Pernomiam, Fabiana Car (2025)
Molar–Incisor Hypomineralization (MIH) is a qualitative defect of enamel development, of multifactorial etiology, affecting permanent molars and incisors. It may compromise stomatognathic functions and negatively impact children’s quality of life. Clinical manifestations include demarcated opacities, dentin hypersensitivity, post-eruptive enamel breakdown, and increased susceptibility to caries—conditions that can result in masticatory, respiratory, and feeding difficulties. This cross-sectional observational study aimed to comparatively analyze orofacial functions in individuals with and without MIH. The sample consisted of 56 children aged 6 to 12 years, evaluated using the Nordic Orofacial Test–Screening (NOT-S), the Schiff Cold Air Sensitivity Scale (SCASS), and the Visual Analogue Scale (VAS) for pain. The results demonstrated a significant impact of MIH on dental sensitivity and mastication. Children with MIH exhibited higher pain intensity on the VAS (p = 0.035) and significantly stronger responses to thermal stimulation (p < 0.001), confirming pronounced dentin hypersensitivity. In the NOT-S, the mastication domain was the only one showing a statistically significant difference between groups (p = 0.029), indicating impaired masticatory efficiency. Although statistically significant differences were not observed in respiratory or other orofacial domains, a higher frequency of alterations was identified in the MIH group, suggesting possible functional repercussions not detected within the cross-sectional design. It is concluded that MIH directly interferes with orofacial functions, particularly mastication, in association with increased oral sensitivity. These findings reinforce the need for interdisciplinary evaluation and early management strategies to prevent adverse effects on craniofacial growth and development.